The complete guide to finishing basements + garages : projects and practical solutions for finishing basements and upgrading garages. (Cool Springs Press, 2024)
In BLACK+DECKER The Complete Guide to Finishing Basements and Garages 3rd Edition, you'll find a deep dive into various projects that will help you make the most of your home. Heal cracks in your foundation wall, pest-proof your basement, install a mini-split system, and so much more. Whether you're already underway creating a new addition to your house or looking for a guide to get your creative juices flowing, this book is a great fit.--